Comparison of stress-strain model of FRP-confined concrete in circular and square section - Gustriyanto (Nanyang Technological University, 2020)
Structural reinforcing by the use of fibre-reinforced polymer (FRP) composites has found increasingly wide applications in civil engineering because of their high strength-to-weight ratio and excellent corrosion resistance. Reliable design of these structural elements requires a clear understanding and accurate modelling of the stress-strain behaviour of FRP-confined concrete. Therefore, to model the mechanical behaviour of FRP-confined concrete, peak strength and ultimate strain are necessary to be defined. This paper presents a review of nine circular section models and eight square section models developed to predict the ultimate axial stress and ultimate axial strain of FRP-confined concrete. This comparison was diversified by the cross-sectional shape and type of FRP (CFRP, GFRP, AFRP). The accuracy of each existing proposed model was then evaluated using this database, and the outcome of this evaluation was shown through absolute average error. At the end of the paper, a conclusion of the best performance of the model is presented.